AB0274 Impact of Baseline Anti-Cyclic Citrullinated Peptide 2 Antibody Titre on Efficacy Outcomes Following Treatment with Subcutaneous Abatacept or Adalimumab: 2-Year Results from the Ample Trial. (9th June 2015) - Sokolove, J.; Schiff, M.; Fleischmann, R.; Weinblatt, M.E.; Connolly, S.E.; Johnsen, A.; Zhu, J.; Maldonado, M.A.; Patel, S.; Robinson, W.H.
Abstract : Background: The head-to-head AMPLE (Abatacept versus Adalimumab Comparison in Biologic-Naïve RA Subjects with Background Methotrexate) study provides a unique opportunity to compare the treatment and mechanistic effects of a T-cell co-stimulation modulator versus a TNF inhibitor. 1 In patients (pts) with RA, the predictive value of baseline (BL) titres of anti-citrullinated protein antibodies (ACPA), a known biomarker for RA and disease progression, 2-3 on treatment outcomes is not well understood. This information may serve as a valuable predictor of response to specific treatments. Objectives: To assess the efficacy of SC abatacept (ABA) and adalimumab (ADA) in pts with different BL levels of anti-cyclic citrullinated peptide 2 (CCP2) antibodies (a surrogate for ACPA). Methods: In this post hoc analysis of the AMPLE study, pt samples were analysed by anti-CCP2 immunoglobulin (IgG) ELISA 4 and efficacy outcomes were assessed in positive pts divided into equal quartiles (Q) based on BL titre. Q1 to Q4 represent increasing titres of anti-CCP2 antibody. Efficacy outcomes analysed by Q were: mean change from BL in DAS28 (CRP) and HAQ-DI over time, and remission rates in terms of CDAI, SDAI and DAS28 [CRP] <2.6 defined remission. Mean change from BL was determined by analysis of covariance, with treatment and DAS28 (CRP) stratification as factors, and BL values as a covariate. Data are also presented for change from BL in DAS28 (CRP) over time in pts who were anti-CCP2 antibody negative at BL. Results: There were 97 pts per Q. The numbers of pts per treatment group in each Q were (ABA, ADA): Q1=42, 55; Q2=51, 46; Q3=46, 51; Q4=46, 51. Overall BL characteristics were generally comparable, with no discernible pattern across Qs and treatment groups. For example, pts in ABA Q4 and ADA Q2 had numerically higher DAS28 (CRP) but lower HAQ-DI scores than pts in other Qs. For ABA, mean improvements from BL in DAS28 (CRP) and HAQ-DI were greater in the highest titre anti-CCP2 Q compared with the other Q. The 95% CI of these measures for the highest and lowest titre Q did not overlap. Adjusted mean change from BL in DAS28 (CRP) over time by BL anti-CCP2 Q, including pts anti-CCP2 negative at BL, is shown in the Figure . The reduction in DAS28 (CRP) and HAQ-DI by Year 2 were generally comparable in Q1–3 in both ABA and ADA treatment groups; there was no apparent association between these efficacy measures and BL anti-CCP2 titre in the ADA group. Remission rates across all indices were broadly similar in ABA and ADA groups in Q1–3, but were numerically greater in Q4 compared with Q1–3 in the ABA treatment group only. Conclusions: Higher titre anti-CCP2 antibody at BL is correlated with better efficacy in pts from the AMPLE study treated with abatacept, but not with adalimumab. References: Verpoort KN, et al. Arthritis Rheum 2006;54:3799–808. Schiff M, et al. Ann Rheum Dis 2014;73:86–94. Anti-CCP2 ELISA, Euro Diagnostica. http://www.eurodiagnostica.com/upload/files/fileLibrary/ProductSheet_CCPlus_Screen120504.pdf . Accessed 15 Jan 2015 Disclosure of Interest: J. Sokolove Grant/research support from: Bristol-Myers Squibb, M. Schiff Grant/research support from: UCB, Consultant for: AbbVie, Amgen, Antares, Bristol-Myers Squibb, Eli Lilly, Horizon, Johnson and Johnson, Novartis, Novo Nordisk, Pfizer, Roche, UCB, Speakers bureau: AbbVie, R. Fleischmann Grant/research support from: AbbVie, Amgen, Astellas, AstraZeneca, Bristol-Myers Squibb, Celgene, Dynavax, Genzyme, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Roche, sanofi-aventis, UCB, Xoma, Consultant for: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Pfizer, Roche, sanofi-aventis, UCB, M. E. Weinblatt Grant/research support from: Bristol-Myers Squibb, Crescendo Bioscience, UCB, Consultant for: Bristol-Myers Squibb, Crescendo Bioscience, UCB, AbbVie, Roche, Janssen, Pfizer, Lilly, Amgen, S. E. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, A. Johnsen Employee of: Bristol-Myers Squibb, J. Zhu Employee of: Bristol-Myers Squibb, M. A. Maldonado Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Patel Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, W. H. Robinson: None declared